Genistein treatment increases bone mass in obese, hyperglycemic mice - Michelin, Richard M (Diabetes Metab Syndr Obes, 2016)
BACKGROUND: Obesity and type 2 diabetes mellitus are associated with elevated risk of limb bone fracture. Incidences of these conditions are on the rise worldwide. Genistein, a phytoestrogen, has been shown by several studies to demonstrate bone-protective properties and may improve bone health in obese type 2 diabetics. METHODS: In this study, we test the effects of genistein treatment on limb bone and growth plate cartilage histomorphometry in obese, hyperglycemic ob/ob mice. Six-week-old ob/ob mice were divided into control and genistein-treated groups. Genistein-treated mice were fed a diet containing 600 mg genistein/kg for a period of 4 weeks. Cross-sectional geometric and histomorphometric analyses were conducted on tibias. RESULTS: Genistein-treated mice remained obese and hyperglycemic. However, histomorphometric comparisons show that genistein-treated mice have greater tibial midshaft diameters and ratios of cortical bone to total tissue area than the controls. Genistein-treated mice also exhibit decreased growth plate thickness of the proximal tibia. CONCLUSION: Our results indicate that genistein treatment affects bone of the tibial midshaft in the ob/ob mouse, independent of improvements in the hyperglycemic state and body weight.